Improving Primary Care After Stroke (IPCAS) randomised controlled trial: protocol for a multidimensional process evaluation. Issue 7 (8th July 2020) - Aquino, Maria Raisa Jessica (Ryc); Mullis, Ricky; Kreit, Elizabeth; Johnson, Vicki; Grant, Julie; Lim, Lisa; Sutton, Stephen; Mant, Jonathan
Abstract : Introduction: Primary care interventions are often multicomponent, with several targets (eg, patients and healthcare professionals). Improving Primary Care After Stroke (IPCAS) is a novel primary care-based model of long-term stroke care involving a review of stroke-related needs, a self-management programme, a direct point of contact in general practice, enhanced communication between care services, and a directory of national and local community services, currently being evaluated in a cluster randomised controlled trial (RCT). Informed by Medical Research Council guidance for complex interventions and the Behaviour Change Consortium fidelity framework, this protocol outlines the process evaluation of IPCAS within this RCT. The process evaluation aimed to explore how the intervention was delivered in context and how participants engaged with the intervention. Methods and analysis: Mixed methods will be used: (1) design: intervention content will be compared with 'usual care'; (2) training: intervention training sessions will be audio/video-recorded where feasible; (3) delivery: healthcare professional self-reports, audio recordings of intervention delivery and observations of My Life After Stroke course (10% of reviews and sessions) will be coded separately; semistructured interviews will be conducted with a purposive sample of healthcare professionals; (4) receipt and (5) enactment: where available, structured stroke review records will be analysed quantitatively; semistructured interviews will be conducted with a purposive sample of study participants. Self-reports, observations and audio/video recordings will be coded and scored using specifically developed checklists. Semistructured interviews will be analysed thematically. Data will be analysed iteratively, independent of primary endpoint analysis. Ethics and dissemination: Favourable ethical opinion was gained from Yorkshire & The Humber-Bradford Leeds NHS Research Ethics Committee (19 December 2017, 17/YH/0441). Study results will be published in a peer-reviewed journal and presented at relevant conferences. Trial registration number: NCT03353519 ; Pre-results.